Anatomic evaluation of temporomandibular joint using magnetic resonance imaging. Review article - Lévano Loayza, Sandro Alexander (2021)
To develop a systemic and synthetic review of temporomandibular joint anatomy on magnetic resonance images for evaluation. Temporomandibular joint is an anatomical structure made up of bones, muscles, ligaments, and an articular disc that allows important physiological movements to be made, such as opening, closing, protrusion, retrusion, and mandibular lateralization. Magnetic resonance is an imaging technique that does not use ionizing radiation and is more specific for soft tissues evaluation and interpretation, due to its high resolution, which is why it has an important role in various maxillofacial pathologies diagnosis, reason by which dentist must have temporomandibular joint structures and functions knowledge by means of magnetic resonance images. The review demonstrates magnetic resonance imaging importance in the study of temporomandibular joint anatomy study, in addition to mentioning the advantages that this imaging technique provides, such as its good soft tissues detail in their different sequences and the non-use of radiation. ionizing to obtain your images.